Tagesangebot in the Little Prussian Book - Lemeškin, Ilja (Baltistica, 2024)
The medieval “Little Prussian Book,” included in S. Grunau’s 16th-century Preussische Chronik, represents a Hanseatic lexicographical production (bilingual and utilitarian). This article reconstructs (corrects) the structure of the 13th-century original. I analyse a group of nouns located between the thematic chapters of the glossary and the conversations, which can be interpreted as a listing of items for sale as a “daily offer”.